Assessing the Measurement Properties of the Test of Gross Motor Development-3 Using the COSMIN Methodology—A Systematic Review - Yuanye Zhu; Jing Wang; Yaru Ding; Yongdong Qian; Mallikarjuna Korivi; Qian Chen; Weibing Ye (Behavioral Sciences)
This study aimed to systematically review the measurement properties of the Test of Gross Motor Development-3 (TGMD-3) using the COSMIN methodology. A search of four databases (PubMed, EMBASE, Web of Science, CINAHL) identified 23 relevant studies. The methodological quality of the studies was assessed using the COSMIN risk of bias checklist; the measurement properties of the TGMD-3 were evaluated by the COSMIN quality criteria; and the quality of the evidence was rated using a modified GRADE approach. The findings indicated that the test–retest, inter-rater, and intra-rater reliability, as well as measurement invariance and part content validity (relevance and comprehensibility), were sufficient, supported by high-quality evidence. The bifactor structure was found to be a more appropriate model for the TGMD-3, with structural validity and internal consistency rated as sufficient, though based on moderate-quality evidence. However, hypothesis testing for construct validity produced inconsistent results, also supported by moderate-quality evidence. Responsiveness was rated as inconsistent, based on low-quality evidence. Overall, the TGMD-3 is graded as “B”, meaning it has the potential to be recommended, but further research is needed to fully establish its measurement properties. Future studies should focus on verifying the comprehensiveness of items of the TGMD-3 to optimise its application.